PERANCANGAN KONSTRUKSI FORK PADA AUTOMATED STORAGE AND RETRIEVAL SYSTEM (AS/RS) - Adrian Adrian; Agus Halim; Agustinus Purna Irawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Along with the times, there have been considerable changes in various fields. One of them is technology. Developments in this field play an important role for humans in carrying out their activities. In general, the application of inventory management is a major factor in every business. In inventory management activities, a support mechanism is needed to ensure the effectiveness of inventory management activities. The support is in the form of a machine that is able to coordinate the placement of storage or retrieval of a material, material, and so on for the next stage. Automated Storage and Retrieval System (AS/RS) is one of the options for the existing problems. The load that the fork can accommodate on the AS/RS engine is about 2 tons. So from these needs, the components are designed or designed in such a way as to be able to accept the load of about 2 tons during the operation process. The research method used is a systematic method. This is with the aim of getting a more structured explanation of the AS/RS fork design. Warehousing systems that use conventional methods to store and retrieve goods will affect the company's productivity. In design, there are several basic factors that are important to be resolved, namely mechanical design and construction design. The mechanical design is related to the working mechanism of the Automatic Storage and Retrieval System. While the design is related to the design for the Automated Storage and Retrieval System. In general, the implementation of the Automated Storage and Retrieval System, is very helpful for many industries in terms of inventory management.Seiring dengan perkembangan zaman, terjadi perubahan yang cukup besar di berbagai bidang. Salah satunya adalah teknologi. Perkembangan di bidang ini sangat memegang peranan penting bagi manusia dalam menjalankan aktivitasnya. Secara umum pengaplikasian manajemen inventaris menjadi faktor utama dalam setiap bisnis. dalam kegiatan manajemen inventaris, dibutuhkannya sebuah mekanisme penyokong yang menjamin keefektivitasan kegiatan manajemen inventaris. Penyokong tersebut berupa mesin yang mampu mengkoordinasikan penempatan penyimpanan atau pengambilan suatu bahan, material, dan sebagainya untuk dilakukan tahapan selanjutnya. Automated Storage and Retrieval System (AS/RS) menjadi salah satu opsi dari permasalahan yang ada. Beban yang mampu ditampung oleh fork pada mesin AS/RS yaitu sekitar 2 ton. Sehingga dari kebutuhan tersebut, komponen dirancang atau didesain sedemikian rupa untuk mampu menerima beban sekitar 2 ton tersebut selama proses pengoperasiaannya. Metode penelitian yang digunakan adalah metode sistematik. Hal ini dengan tujuan mendapatkan penjelasan lebih terstruktur mengenai perancangan fork AS/RS. Sistem pergudangan yang menggunakan cara konvensional untuk menyimpan dan mengambil barang akan mempengaruhi produktivitas perusahaan. Dalam desain, ada beberapa faktor dasar yang penting untuk diselesaikan, yaitu desain mekanis dan desain konstruksi. Desain mekanis terkait dengan mekanisme kerja Sistem Penyimpanan dan Pengambilan Otomatis. Sedangkan desain terkait dengan desain untuk Automated Storage and Retrieval System. Secara umum, penerapan Automated Storage and Retrieval System, sangat membantu banyak industri dalam hal pengelolaan persediaan.